Commodification and the Performative Sign in the Eucharistic Ethics of Luther and Calvin. (13th November 2017) - Hawkes, David
Abstract: This article calls attention to the need for an ethics of representation. The practical power of signs, symbols and images is obvious all around us. It is pre-eminent in the economy, which has undergone a process of financialization to the extent that it is now dominated by the performative financial signs known as 'derivatives.' In early modern Europe, at the dawn of capitalism, people engaged in an extended debate about the ethics of performative representation. That discussion focused on the Eucharist, but this article demonstrates that it was also concerned with the psychological effects of commodification. Such controversies should be interpreted in the light of the twenty-first century economy, in order to elaborate a moral response to the autonomous practical power of representation. This article considers the Eucharistic theories of Luther, Zwingli and Calvin as an initial, partial attempt to develop an ethics of representation for the twenty-first century.